MODEL TRANSFORMASI DIGITAL PENGADAAN BARANG/JASA PEMERINTAH YANG EFEKTIF DAN EFISIEN DALAM RANGKA MEWUJUDKAN GOOD GOVERNANCE - Bustanul Arifun Shodiq; Muhtadi; Satria Prayoga (JURNAL ILMIAH EDUNOMIKA, 2026)
This research aims to examine and formulate an effective and efficient digital transformation of government procurement of goods/services in order to realize the principles of good governance. Government procurement of goods/services is a strategic aspect of clean, transparent, and accountable governance. Digital transformation of the procurement process is one solution expected to minimize corruption, collusion, and nepotism, while simultaneously increasing bureaucratic efficiency and effectiveness. However, in its implementation, digital transformation of procurement still faces various challenges, including regulatory aspects, human resource capacity, technological infrastructure, and institutional resistance. The problem examined in this research is how to model an effective and efficient digital transformation of government procurement of goods/services in order to realize good governance. The research method used is a normative method with a statutory approach and a conceptual approach, and descriptive qualitative analysis is used.  Keywords: Digital Transformation, Procurement of Goods/Services, Good Governance